The studies of Japan by Shokan Ualihanov - Акын, Б. К.; Айтмагамбетова, А. (Journal of Oriental Studies, 2016)
The article deals with the study by Sh.Ualihnov the map data for Japan. The authors clarified aspects of mapping by Sh.Ualihnov somelocalities of provinces of the Land of the Rising Sun. They also compared the information entered by scientist and modern disposition of thesesettlements.